2021
DOI: 10.1002/agj2.20850
|View full text |Cite
|
Sign up to set email alerts
|

Plant density and nitrogen fertilization optimization on sorghum grain yield in Mali

Abstract: Sorghum [Sorghum bicolor (L.) Moench], a staple food crop in Mali, has low yields for several reasons including that many farmers do not have the financial resources to purchase state-of-the-art genetics and fertilizers and information is not available on how to optimize yields for heirloom variety. To improve their economic and environmental sustainability, Mali farmers need to understand how to invest their limited resources. In many situations this involves the use of open-pollinated varieties that have a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
(45 reference statements)
0
10
0
1
Order By: Relevance
“…The study of Moi (2021) confirmed that adding nitrogen to the soil led to an increase in grain yield 265 compared with no addition, by adding two levels of nitrogen fertilizer 80 and 40 kg nitrogen / ha. Dembele et al (2021) show that the level (178 kg N/ ha) was better in the characters PH , chlorophyll leaves content, LAI, no. of spike/ m 2 , , 1000 grain weight and grain yield compare with (zero, 89 Kg N/ha) .…”
Section: Effect Of Nitrogen Fertilizationmentioning
confidence: 91%
See 1 more Smart Citation
“…The study of Moi (2021) confirmed that adding nitrogen to the soil led to an increase in grain yield 265 compared with no addition, by adding two levels of nitrogen fertilizer 80 and 40 kg nitrogen / ha. Dembele et al (2021) show that the level (178 kg N/ ha) was better in the characters PH , chlorophyll leaves content, LAI, no. of spike/ m 2 , , 1000 grain weight and grain yield compare with (zero, 89 Kg N/ha) .…”
Section: Effect Of Nitrogen Fertilizationmentioning
confidence: 91%
“…The study of Sekou et al (2020) found the superiority of the yield of grins plant density 53333 plants/ha over the yield of grain plant density 26666 plants/ha. Dembele et al (2021) found that the plant density 53300 plant /ha was better in the plant height , chlorophyll leaves content, leaf area index, no. of spike/ m 2 , 1000 grain weight and grain yield compared with plant density 26600 plant / ha .…”
Section: Effect Of Plant Densitymentioning
confidence: 97%
“…Berenguer and Faci (2001) indicated that a high plant density did not present a productive advantage in the sorghum grain yield, especially under limited irrigation conditions. However, previous study showed significant interaction of plant density, nitrogen rate, and variety on sorghum grian yield as well (Dembele et al, 2021). Therefore, plant density in terms of grain yield varied with different growing conditions and sorghum varieties; therefore, knowledge of optimum plant density in combination with cultivation conditions and variety will help producers boost sorghum productivity.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, potential genetic variability for N uptake and utilization efficiency exists and can be exploited by evaluating larger sets of diverse genotypes with high-throughput phenotyping and genotyping tools. Moreover, sensor-based N application along with integrated agronomic practices such as supplemental irrigation ( Sigua et al, 2018 ), planting density ( Dembele et al, 2021 ) could achieve higher yield and NUE in sorghum. Conversely, a higher genetic diversity has been reported in sorghum for below ground traits as compared to the aboveground traits ( Wojciechowski and Kant, 2021 ).…”
Section: Sensor-based High-throughput Phenotyping For Determining Nit...mentioning
confidence: 99%